Montaje y repotenciación del sistema eléctrico de iluminación del taller mecánico de la Universidad Nacional de Loja. - Villavicencio Castillo, Marco Antonio (2015)
In the research work named “MONTAJE Y REPOTENCIACIÓN DEL SISTEMA ELÉCTRICO DE ILUMINACIÓN DEL TALLER MECÁNICO DE LA UNIVERSIDAD NACIONAL DE LOJA”, it allowed the improvement of lighting in the work area according to the distribution of each machine. With the development of this work, allowed the changing channeling lighting grid, allowing a proper electrical installation using materials necessary for a good and correct operation. The completion of repowering of each lighting circuit, the power lines was moved to the main box which distributes in different circuits to get better the power distribution.